PENINGKATAN PEMAHAMAN DAN KESADARAN ANTI-BULLYING MELALUI LAYANAN INFORMASI DENGAN TEKNIK SOSIODRAMA PADA SISWA KELAS IX C SMP NEGERI 1 JATINEGARA - Sri Lestari (Universitas Sultan Ageng Tirtayasa, 2020)
This study aims to increase the understanding and awareness of anti-bullying in class IX students of SMP Negeri 1 Jatinegara through the provision of information services using socio drama techniques. This is classroom action research with subjects of class IX students of SMP Negeri 1 Jatinegara towards 28 students.. The data collection methods used Likert scale, observation and documentation. The instruments used were anti-bullying awareness and understanding scale, observation and document analysis. The actions used are: power points and bullying videos, discussion and socio drama. In the first cycle use drama scripts, while the second cycle without using drama scripts and the actors were added. The sensing aspect arises in the first cycle, while in the second cycle the aspects of feelings, actions and thoughts. Increased understanding of anti-bullying in the first cycle is 46.42%, and the second cycle of 82.14% which is in the category of very high awareness. Anti-bullying awareness as evidenced by the acquisition of the first cycle of 53.57%, and the second cycle of 85.71%. Based on the criteria made, 75% of students have very high anti-bullying awareness; the results of this study indicate that understanding and awareness of anti-bullying can be improved through the provision of information services using socio drama techniques.